EDUCAÇÃO ESPECIAL: SABERES E ESTRATÉGIAS DOS PROFESSORES DE EDUCAÇÃO INFANTIL - Silva, Aparecida Souza França (2021)
Early Childhood Education, as the first stage of teaching Basic Education, becomes and constitutes an important element that contributes to the child's development. To this end, the school space becomes a favorable place to reflect on human development and training. The research aimed to research and problematize the knowledge and strategies of Early Childhood Education teachers, in the area of Special Education, and how this knowledge guides and organizes their practices in the classroom. As a theoretical and methodological option, we opted for the historical-cultural perspective of human development elaborated by Vigotski. The understanding of pedagogical practices and their influence on the development of children, the target audience of Special Education, guided the studies by Vigotski and his collaborators on defectology in the early 20th century. In this sense, the research is of a qualitative nature and used a focus group as a procedure for data collection. The research participants were teachers, educators and the director of a public institution for Early Childhood Education, in the city of Pedro Canário, ES. The data collected were organized into five categories, with the title: Knowledge and strategies in school daily life and subtitles: 1) The implications of the experiences, values and beliefs of pedagogical practice; 2) The difficulties and needs arising from teaching relationships; 3) What do I think about the diagnoses and reports; 4) The use of methodologies as a contribution to students' social and human development; 5) Professional performance for the human formation process. Therefore, it was found that the direction to follow the alternative paths, which Vigotski teaches us, moves in a double way, from the student with disabilities to the teacher and vice versa. Thus, whenever it is proposed to offer the necessary conditions for student access, whether that student is disabled or not, access to the teacher is also promoted. In this way, socio-psychological compensation is established for both, one can be the guiding thread of the other, as it is in this event that the possibilities emanate, indicative for the process of teaching and learning. How much time will be made available for this feat? It is understood that the research generated strong evidence in relation to the importance of the initial and continuing training of professionals and the improvement in the quality of social relations, as well as the need for greater investment / involvement in collaborative work, the expansion of discussions about reports and the appreciation of teachers. It is expected that the data produced in this study are important indicators for possible investments and improvements in favor of Special Education, given that they echoed from peers who are constituents / participants in this process of building Special Education.